The role of 68Ga-DOTA-TATE PET/CT scanning in the evaluation of patients with multiple myeloma: preliminary results. Issue 1 (January 2017) - Sonmezoglu, Kerim; Vatankulu, Betul; Elverdi, Tugrul; Akyel, Resit; Erkan, Melih E.; Halac, Metin; Ocak, Meltem; Demirci, Emre; Aydin, Yildiz
Abstract : Objective: In this observational pilot study, we aimed to evaluate the role of gallium-68-labelled DOTA-TATE ( 68 Ga-TATE) PET/computed tomography (CT) scanning in patients with multiple myeloma (MM), considering previous promising results obtained from conventional somatostatin receptor scintigraphy with 111 In pentetreotide. Materials and methods: Twenty-one patients with a diagnosis of MM were prospectively included in this study: eight patients were referred for initial staging and 13 patients for restaging purpose. Both fluorine-18 fluorodeoxyglucose ( 18 F-FDG) and TATE PET/CT scanning were performed in all patients. Results: All patients had one or more PET-positive lesion on either 18 F-FDG or TATE scans. Six patients had an additional diffusely increased bone marrow activity on 18 F-FDG scans, five of whom also had a concordant bone marrow appearance on TATE scans. Each PET set (either 18 F-FDG or TATE) was positive in 19 patients. There was a discordant result in four (19%) patients between 18 F-FDG and TATE scans. 18 F-FDG scans showed 112 lesions (86 TATE-positive; 26 TATE-negative) in 19 patients, whereas TATE scans showed 108 lesions (86 18 F-FDG-positive; 22 18 F-FDG-negative) in 19 patients. No significant difference was found between the two modalities in terms of lesion numbers detected ( P =0.67). However, the presence of diffuse bone marrow uptake of TATE seems to be a predicting factor for the overall survival ( P =0.033, hazard ratio: 15.2 and 95% confidence interval: 1.2–185.5). Conclusion: TATE PET/CT seems to be an alternative imaging modality and may play a complementary role in MM management, at least by providing a different pathobiological insight into the disease.